College Students' Satisfaction and Involvement with the Recreation Center Based on Perceived Service Quality: The Moderating Effects of Health and Weight Consciousness. Issue 2 (October 2016) - Suttikun, Chompoonut; Chang, Hyo Jung
A university recreation center is a service provided for students benefiting their physical health while offering relief from some stress from an academic life. Understanding students' perceptions of service quality helps collegiate recreation administrators improve facilities and services to better serve current members. This study examined college students' perceptions of service quality and how perceptions affected their satisfaction and involvement at a recreation center utilizing "health and weight consciousness" as moderators. Results showed that components of service quality, including reliability (e.g., ability to perform the promised services), tangibles (e.g., facilities and equipment), and assurance (e.g., knowledge and courtesy of employees) played critical roles affecting users' satisfaction, and in turn influenced their involvement in the recreation center. Furthermore, users who care more about their health tend to be more satisfied with service quality and are more involved with activities or sports at the recreation center.